2020
DOI: 10.3389/fbioe.2020.590998
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Polydopamine-Modified Scaffolds in the Peripheral Nerve Tissue Engineering

Abstract: Peripheral nerve injury is a common and complicated traumatic disease in clinical neurosurgery. With the rapid advancement and development of medical technologies, novel tissue engineering provides alternative therapies such as nerve conduit transplantation. It has achieved significant outcomes. The scaffold surface modification is vital to the reconstruction of a pro-healing interface. Polydopamine has high chemical activity, adhesion, hydrophilicity, hygroscopicity, stability, biocompatibility, and other pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 66 publications
2
36
0
Order By: Relevance
“…The above results suggested that polydopamine could improve the cell adhesion and proliferation, which may be related to improved hydrophilicity and the abundant catechol-based adhesion groups in polydopamine. 54,55 However, we found a slight decrease in cell proliferation after loading AuNPs on the scaffold surfaces. Loading of AuNPs, a hydrophobic metal substance, could reduce the material surface hydrophilicity and the exposure of the catechol-based adhesive groups on the scaffold surface to some extent, which may affect the early adhesion and proliferation of the cells in a particular range.…”
Section: Cell Proliferation and Adhesionmentioning
confidence: 72%
“…The above results suggested that polydopamine could improve the cell adhesion and proliferation, which may be related to improved hydrophilicity and the abundant catechol-based adhesion groups in polydopamine. 54,55 However, we found a slight decrease in cell proliferation after loading AuNPs on the scaffold surfaces. Loading of AuNPs, a hydrophobic metal substance, could reduce the material surface hydrophilicity and the exposure of the catechol-based adhesive groups on the scaffold surface to some extent, which may affect the early adhesion and proliferation of the cells in a particular range.…”
Section: Cell Proliferation and Adhesionmentioning
confidence: 72%
“…The inhibition of excessive immune responses is of vital importance to restoring the balance in microenvironment after PNIs ( Qian et al, 2019b , 2020a , b ). The treatment of long-gap nerve defects requires highly functional biomimetic scaffolds to bridge the proximal and distal stumps ( Qian et al, 2019a , c ; Chen et al, 2020 ; Yan et al, 2020 ; Yang et al, 2020 ). In contrast, the treatment of severe nerve crush injuries relies more on the pharmacotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Artificial nerve scaffolds hold great promise for the biomedical treatment of injured nerves by connecting the damaged stumps and new nerve tissues form within the scaffold chamber ( Liu et al, 2019 ; Jiang et al, 2020 ; Yan et al, 2020 ; Li et al, 2021 ). However, the functional restoration of PNIs still remains unsatisfactory ( Qian et al, 2018b ; Qian et al, 2019b ; Qian et al, 2019c ).…”
Section: Final Remarksmentioning
confidence: 99%